Indirect effects of COVID-19 Pandemic in ST-segment elevation myocardial infarction: insights from a multicentric national survey. (14th October 2021) - Pereira, H; Cale, R; Farto-Abreu, P; Pereira, E; On Behalf Of Stent Save A Life Initiative, S S L
Abstract: Objective: Coronavirus disease 2019 (COVID-19) pandemic may have indirect consequences in ST-segment elevation myocardial infarction (STEMI) outcomes due to difficulties in healthcare access, but also due to reperfusion delays. The objective of this study was to evaluate the performance indicators in STEMI during the early phase of the lockdown following the COVID-19 pandemic. Methods: The "patient delay" and the "system delay" were evaluated in 312 patients with suspected STEMI, in the period of the first State of Emergency in Portugal, through a survey called "Moment COVID" implemented within 18th March to 2 May 2020, in 18 national centers of Interventional Cardiology where PPCI is carried out 24/7. These patients were compared with a historical cohort of 267 patients from the 5th year after integration of SFL Initiative in Portugal (Moment 2015) in which the same survey was applied. Patients with late presentation of STEMI (>12 hours of symptoms onset) were excluded from this analysis. Results: In "Moment COVID" there was a trend towards a longer "patient delay" (incremental median 20 min; p=0.059) and a significant longer system-delay (incremental median 17 min; p=0.033) compared to the historical cohort of "Moment 2015". Consequently, times to revascularization tended to be longer (incremental median 26 min; p=0.074). Indeed, in "Moment COVID" patients were less compliant with the times recommended by the European guidelines: door-to-balloon time <60 min was achieved in 47.6% of patients compared to 57.0% (p=0.052) in "Moment 2015" and system-delay <90 min in 13.9% compared to 21.8% (p=0.033). Conclusion: These results from a multicentric national analysis demonstrated a trend to longer time from symptom onset to request healthcare system assistance and a significantly longer time from first medical contact to revascularization among patients with STEMI during COVID-19 pandemic. This delay for treatment could negatively impact the STEMI prognosis at the long-term. Funding Acknowledgement: Type of funding sources: None.